2021
DOI: 10.1152/ajpregu.00246.2020
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the carotid body increases directly recorded cardiac sympathetic nerve activity and coronary blood flow in conscious sheep

Abstract: Activation of the carotid body (CB) using intracarotid potassium cyanide (KCN) injection increases coronary blood flow (CoBF). This increase in CoBF is considered to be mediated by co-activation of both the sympathetic and parasympathetic nerves to the heart. However, whether cardiac sympathetic nerve activity (cardiac SNA) actually increases during CB activation has not been determined previously. We hypothesized that activation of the CB would increase directly recorded cardiac SNA, which would cause coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 60 publications
2
15
2
Order By: Relevance
“…Previous papers have shown that carotid chemoreflex stimulation by nicotine causes coronary vasodilation in conscious control animals mediated by parasympathetic cholinergic efferent fibers (Hackett et al, 1972;Shen et al, 1994) although this is to contrast to our previous study (Pachen et al, 2020). In our present study, the increased CoBF in both control and HF sheep in response to CB stimulation were unchanged following intravenous atropine infusion.…”
Section: Effect Of Atropine On Carotid Chemoreceptor Stimulationcontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous papers have shown that carotid chemoreflex stimulation by nicotine causes coronary vasodilation in conscious control animals mediated by parasympathetic cholinergic efferent fibers (Hackett et al, 1972;Shen et al, 1994) although this is to contrast to our previous study (Pachen et al, 2020). In our present study, the increased CoBF in both control and HF sheep in response to CB stimulation were unchanged following intravenous atropine infusion.…”
Section: Effect Of Atropine On Carotid Chemoreceptor Stimulationcontrasting
confidence: 99%
“…(Pachen et al, 2020). Importantly, infusion of the non-selective beta-blocker propranolol abolished the increase in CoBF (Pachen et al, 2020). We concluded that the β2-adrenergic vasodilatory actions supersede the alpha receptor vasoconstriction during reflex sympathetic activation and are responsible for the coronary vasodilatation.…”
Section: The Arterial Pressure Responses To Cb Activation In Control and Hfmentioning
confidence: 76%
See 2 more Smart Citations
“…CB activation increases sympathetic activity and also simultaneously increases cardiac vagal as well as cardiac sympathetic nerve activity, causing HRV. 33 , 34 OSA patients also have high sympathetic activity, even during normoxic wakefulness. 35 HRV is a common quantitative index for evaluating sympatho-parasympathetic balance, 36 which makes it a promising indicator of CBC.…”
Section: Discussionmentioning
confidence: 99%